Baseball and biomechanics: Injury prevention for baseball pitcher - Irawan, Fajar Awang; Long-Ren, Chuang (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2019)
Pitching was the fastest motion in baseball. Upper extremity has important roles especially in shoulder, elbow, wrist, and fingers. The purpose of this study was to integrate the information in a resume of biomechanical pitching and baseball pitcher’s injuries. The data base used refers to PubMed, SAGE, and Elsevier and several relevance journals related to baseball and injuries. Source refers to the data since December 2017 to the oldest 2000 to get data source in baseball pitcher injuries. Upper arm has the prominent role when pitching to get maximum motion and joints stabilize. Rotator cuff muscle generate rotation in the shoulder while pitching and control shoulder joints in the lower arm’s muscles and joints. Baseball pitcher has a special skill in the strength, speed, and endurance. They had to keep their performance to avoid from injury especially shoulder and elbow injuries. Biomechanical analysis can help to evaluated performance in monitoring dan give recommendation to elevate skills and prevent injury. Knowledge and understanding about basic of pitching have to mastering before elevate to the next level. Further study can focus on the time for the pitcher to improve the skills and maximizing the pitch type to avoid from injuries.